What is an appropriate business model for 'Community Energy Storage' in the UK? - YATHEENDRANATHAN, NISHANTH (2014)
If the UK is to deliver on the legislated 80% carbon reduction by 2050, there are significant technology gaps that need closing. The lack of suitable planned energy storage is at the top of the list. The ability to store energy is a key component to ensure national security. The huge investments in renewable energy will have little value unless some of the energy storage issues are resolved as soon as possible. Much of the DECC’s focus has been to help deliver large national infrastructure projects, however, these reforms will also provide real opportunities for local communities to help meet the challenge of affordable energy security in a low carbon economy.